2011
DOI: 10.1093/nar/gkr784
|View full text |Cite
|
Sign up to set email alerts
|

Tight cooperation between Mot1p and NC2β in regulating genome-wide transcription, repression of transcription following heat shock induction and genetic interaction with SAGA

Abstract: TATA-binding protein (TBP) is central to the regulation of eukaryotic transcription initiation. Recruitment of TBP to target genes can be positively regulated by one of two basal transcription factor complexes: SAGA or TFIID. Negative regulation of TBP promoter association can be performed by Mot1p or the NC2 complex. Recent evidence suggests that Mot1p, NC2 and TBP form a DNA-dependent protein complex. Here, we compare the functions of Mot1p and NC2βduring basal and activated transcription using the anchor-aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 47 publications
(105 reference statements)
3
27
0
Order By: Relevance
“…The differential sensitivity of TATA-containing versus TATA-less promoters may be attributable to their regulation by different coactivator complexes. The SAGA complex loads TBP onto TATA-containing promoters (47) and is also associated with high TBP turnover (40), suggesting that it synergizes with Mot1 in TBP removal, a hypothesis supported by the finding of negative genetic interaction between Mot1 and SAGA (17). In contrast, TATA-less promoters tend to be regulated by the TFIID coactivator complex (47).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The differential sensitivity of TATA-containing versus TATA-less promoters may be attributable to their regulation by different coactivator complexes. The SAGA complex loads TBP onto TATA-containing promoters (47) and is also associated with high TBP turnover (40), suggesting that it synergizes with Mot1 in TBP removal, a hypothesis supported by the finding of negative genetic interaction between Mot1 and SAGA (17). In contrast, TATA-less promoters tend to be regulated by the TFIID coactivator complex (47).…”
Section: Discussionmentioning
confidence: 97%
“…Presumably, loss of TBP at TATA-less promoters would result in decreased expression of the associated genes, while gain of TBP at TATA-containing promoters would increase gene expression. Indeed, it has been shown that AA-mediated depletion of Mot1 tends to reduce the expression of TATA-less genes (17). To ascertain the biological significance of changes in TBP binding that occur when Mot1 is inactivated, we plotted the change in TBP occupancy at promoters as a heat map ranked by the expression of the associated gene in the mot1-42 mutant strain versus control (16).…”
Section: Global Mapping Of Mot1 and Tbp On Native Chromatinmentioning
confidence: 99%
See 1 more Smart Citation
“…The select validation of the enrichment of Ncb2 data points that the higher occupancy of the regulator does not necessarily result in the transcriptional activation as the expression of several genes was also repressed. Notwithstanding, the dual role of Ncb2, the genome-wide occupancy profiling reaffirmed its role as a global regulator of gene expression4660.…”
Section: Discussionmentioning
confidence: 90%
“…Promoter sequences contain TFBS that recruit (TFs) and assemble the transcription preinitiation complex that guides RNA polymerase II to the transcription start site 47. The location of promoters relative to genes, usually located just upstream of a gene, has facilitated their identification and annotation (figure 1A).…”
Section: Dna Regulatory Elementsmentioning
confidence: 99%